Efficient Financial Management of Urban Transport - a Case Study - Teixeira, Sérgio Jesus (2020)
The instability of the markets and trends of tourist activity present challenges to the companies’ managers that work in that sector. How to best prepare for the economic environment, so that companiescan generate profit with the financial instruments and resources available. This work tries to analyze the financial parts, to measurethe performance of a transport company in the Region, and through the literature review, to analyze the impact of an efficient management in the company. The results obtained allowed to conclude that the company “Horários do Funchal Transportes Públicos SA” is in the right direction regarding financial balance.